Contemporary differences between bicuspid and tricuspid aortic valve in chronic aortic regurgitation. Issue 11 (27th October 2020) - Yang, Li-Tan; Benfari, Giovanni; Eleid, Mackram; Scott, Christopher G; Nkomo, Vuyisile T; Pellikka, Patricia A; Anavekar, Nandan S; Enriquez-Sarano, Maurice; Michelena, Hector I
Abstract : Objective: To comprehensively explore contemporary differences between bicuspid aortic valve (BAV) and tricuspid aortic valve (TAV) patients with chronic haemodynamically significant aortic regurgitation (AR). Methods: Consecutive patients with chronic ≥moderate-severe AR from a tertiary referral centre (2006–2017) were included. All-cause mortality, surgical indications and aortic valve surgery (AVS) were analysed. Results: Of 798 patients (296 BAV-AR, age 46±14 years; 502 TAV-AR, age 67±14 years, p<0.0001) followed for 5.5 (IQR: 2.9–9.2) years, 403 underwent AVS (repair in 96) and 154 died during follow-up. The 8-year AVS incidence was 60%±3% versus 53%±3% for BAV-AR and TAV-AR, respectively (p=0.014). The unadjusted (real-life) 8-year total survival was 93%±7% versus 71%±2% for BAV-AR and TAV-AR, respectively (p<0.0001), and became statistically insignificant after sole adjustment for age (p=0.14). The within-group relative risk of death in BAV-AR patients demonstrated a large age-dependent increase (two fold at 50–55 years, up to 10-fold at 70 years). The presence of baseline symptoms was significantly associated with death for both BAV-AR (p=0.039) and TAV-AR (p<0.0001), but the strength of the association decreased with age adjustment for BAV-AR (age-adjusted HR 2.43 (0.92–6.39), p=0.07) and not for TAV-AR (age-adjusted HR, 2.3 (1.6–3.3), p<0.0001). As compared with general population, TAV-AR exhibited baseline excess risk which further increased at left ventricular ejection fraction (LVEF) <60% and left ventricular end-systolic dimension index (LVESDi) >20 mm/m 2 ; similar thresholds were observed for BAV-AR patients. Conclusion: BAV-AR patients were two decades younger than TAV-AR and underwent AVS more frequently, resulting in a considerable real-life survival advantage for BAV-AR that was determined primarily by age and not valve anatomy. Pragmatically, regardless of valve anatomy, patients with haemodynamically significant AR and age >50–55 years require a low-threshold for surgical referral to prevent symptom development where LVEF <60% and LVESDi >20 mm/m 2 seem appropriate referral thresholds.